Obyek Falsafah Al-Qur’an - Khadhary, Muhammad; Dja’fara, Syahril (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2023)
This study aims to explain the object of the philosophy of the Qur’an by beginning with an explanation of the signs of the Qur’an about the source of knowledge, namely: first, the universe; second, human reason itself; third, the source of knowledge that comes from revelation. In addition, the method of obtaining knowledge is also explained, namely first, knowledge is obtained by humans through sensory perception (al-h}issi> ) or it can also be said through empirical experience (al-tajri>bah), second, through the baya>ni method (language analysis), third, through analysis of logical and rational thinking (naz}ariyah ‘aqliyah) or in the popular term burha>ni method, fourth, through intuition and contemplation or ma’rifat al-qalb after going through the riya>d}ah process and muja>hadah so that muka>syafah occurs, or better known as the ‘irfa>ni method, and fifth, through revelation and direct testimony (syaha>dah) of trusted people for the revelation to the prophet God, otherwise known as the al-matlu> method.